Microstructural evolution of a hot-rolled microalloyed complex phase steel. (2nd January 2017) - Scott, H.; Sidhu, G.; Fazeli, F.; Pilkey, A. K.; Boyd, J. D.
ABSTRACT: The current study examines a grade of hot-rolled and continuously cooled complex phase sheet steel comprised of polygonal ferrite (PF), granular bainite (GB) and lath bainite (B). The quantity of each constituent phase depends on the thermomechanical processing conditions, which vary between commercially produced sheets. In this study, the effects of cooling rate and austenite grain morphology on microstructure are determined through a series of dilatometry experiments. The resulting CCT diagrams show a progression in the order PF → GB → B with increasing cooling rate, and that a Pancaked (unrecrystallised) austenite condition promotes the formation of PF to higher cooling rates and the formation of GB to higher temperatures. Application of the CCT results to industrially produced sheet provides a useful approach for interpreting the evolution of microstructure during controlled-cooling and coiling. However, direct comparison is limited by the moderate level of austenite pancaking that can be achieved through laboratory dilatometry experiments in comparison to an industrial hot mill. Notable differences in microstructure are observed between the leading and trailing edges of industrially produced sheets due to relatively small variations in cooling schedules.